Urban Tribes: Subcultures and Political Conflict in West Berlin, 1945-1991 - Clarkson, Alexander (Social justice, 2011)
The article discusses the treatment of subcultures in West Berlin, Germany between 1945-1991, particularly focusing on the construction of juvenile delinquency among West German politicians. It addresses the proliferation of subcultures in the post-World War II period, as well as comments on the belief in the moral degeneration of youth within the West German political discourse. Other topics explored include the emergence of immigrant subcultures in West Berlin, the politicization of subcultures in postwar West Germany, and the impact of globalization on popular conceptions of subcultures.